Down-selection of the VAR2CSA DBL1-2 expressed in E. coli as a lead antigen for placental malaria vaccine development - Chêne, Arnaud; Leroy, Odile; Havelange, Nicolas; Viebig, Nicola (npj vaccines, 2018)
A mix of the right parasitic protein with the right production method has yielded a vaccine candidate for placental malaria. Primarily affecting first-time pregnant women, placental malaria is estimated to cause 200,000 infant deaths and 10,000 maternal deaths annually. In this study, led by Benoît Gamain, researchers from France’s INSERM and Germany’s European Vaccine Initiative assayed a combination of proteins designed to target and block a key pathogenic mechanism of parasite-infected red blood cells. Finding the highest performing protein, the researchers also used an Escherichia coli expression system able to replicate and fold the complex protein correctly. During tests, this protein/vector combination bested others in production qualities and immunogenicity. The team’s efforts laid the foundations for a scalable, low-cost vaccine that is currently undergoing clinical trials.
Gesehen am 23.04.2019